Los puños de una nación: el boxeo y los avatares de la construcción de la identidad nacional panameña - Andrea Cabezas Vargas (IdeAs)
Throughout its history, boxing has been seen as a terrain where competition goes beyond winning a boxing title. Thus, the pairing of pugilism and cinema have transformed over time into an element of entertainment as well as an instrument of communication, support for political trends, and even a mechanism to mobilize nationalist sentiments. Panama is a living example of the complex and tight-knit relationship between politics and boxing. Based on a study of the Central American country, this article seeks to analyze how the full-length documentary Los puños de una nación (2005) by the Panamanian director Pituka Ortega-Heilbron depicts and examines the analogies between boxing, politics, the reconstruction of national identity and the history of Panama.